DEVELOPMENT OF COMMUNICATION POSSIBILITIES BETWEEN PARTICIPANTS OF THE TEMPORARY CHILD GUARDIANSHIP SITUATION: THE RELATION OF VARIABLES - Alifanoviene, Daiva; Vaitkeviciene, Asta; Kauneckiene, Dovile; Orska, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Based on the quantitative research results, the article deals with communication peculiarities of the participants of the temporary child guardianship situation – children and their biological parents whose parental rights are temporarily limited – at the temporary foster care institution in the aspect of specialists working there. Using descriptive mathematical statistics and statistical analysis methods, specialists’ opinion about the causes of disagreements between specialists and learners, the causes of disagreements between  parents and specialists, and communication development possibilities of the participants of the temporary child guardianship situation were analysed.